ASSESSMENT PERENCANAAN PEMBELAJARAN GURU DI SMA NURUL MUTTAQIN ALBAROKHAH KOTA MALANG - Wiwin Ni’maturrohmah (Universitas Yudharta Pasuruan, 2020)
Learning planning is the first step that teachers must prepare before teaching. This study method uses qualitative, with the subject of teacher research in SMA Nurul Muttaqin Albarokhah Malang. The results of this study indicate that teachers at SMA Nurul Muttaqin Albarokhah Malang always prepare learning tools, materials, strategies / methods, media, evaluation of learning, and mentality in the teaching process. Stages in the preparation of planning teaching materials are carried out by preparing learning tools, preparing and choosing methods, strategies, media, and class assessments, as well as looking for materials by looking at the grade level / abilities of students. The constraints found in the planning process are influenced by students, teachers, and the limited facilities and infrastructure at the school.